Relationship between individual metabolic rate and patch departure behaviour: evidence from aquatic gastropods. Issue 11 (4th August 2020) - Cozzoli, Francesco; Shokri, Milad; Ligetta, Giovanna; Ciotti, Mario; Gjoni, Vojsava; Marrocco, Vanessa; Vignes, Fabio; Basset, Alberto
Abstract : Individual energy requirements are tightly related to individual resource use and by extension of space‐use patterns and other traits at higher levels of the ecological hierarchy. However, there is still little experimental evidence linking individual energetics and space‐use behaviour. Individual energy requirements scale mainly with body size and temperature, but these do not explain all individual variation. Therefore, studies focused on inter individual variation in resource and space use behaviour can be used to frame foraging dynamics in an energy perspective. We empirically tested the hypothesis of a relationship between individual energetics and patch departure behaviour using as model organisms four small species (body mass ranging from 0.4 to 14 mg AFDW) of aquatic gastropods strongly differing in adult size: Galba truncatula, Bithynia tentaculata, Theodoxus fluviatilis and Ecrobia ventrosa (in descending order of size). Motility tests were performed in controlled microcosm conditions. The tests were designed to classify the specimens as either low motility (not inclined to abandon the patch) or high motility (likely to abandon the patch). The tests entailed measuring the propensity of the individuals to abandon a limited resource patch (2 g DW of conditioned Phragmites australis leaves) within a given amount of time (24 h) when foraging with conspecifics under conditions where competition for food is expected to increase over time due to resource depletion. The individual standard metabolic rate of the tested specimens was measured via open flow respirometry and compared across motility classes at intra‐ and interspecific level. At both levels, we observed that individuals with higher standard metabolic rates were more inclined to abandon the patch. This finding establishes a link between foraging theory and competitive coexistence mechanisms.